MENINGKATKAN POTENSI USAHA UMKM GAMBART MELALUI MEDIA SOSIAL - Anggraini, Feny Savira; Atikah, Fifi; Taqiyyah, Mia Risyah; Sulaeman, Sania Khaira Ikhsanti; Nurlela, Siti (LPPM Universitas Nusa Mandiri, 2023)
This research aims to explore the potential of TikTok social media utilization in improving the business of MSMEs